Hogyan váljanak többnyelvűvé a kisebbségek? - Csernicskó István; Черничко Степан; Csernicsko Istvan (Pannon Egyetem, 2020)
Az Ukrajna Legfelsőbb Tanácsa (parlamentje) által 2017. szeptember 5‐én fogadta el az új ukrán oktatási kerettörvényt (Ukrajna törvénye, 2017).1 A jogszabály és főként annak 7. cikke azóta a viták kereszttüzében áll mind Ukrajnán belül, mind pedig az ország nemzetközi kapcsolataiban (Beregszászi–Csernicskó, 2017, Csernicskó, 2018a; Fedinec–Csernicskó, 2017). A feszültség középpontjában az áll, hogy az 1991‐ben függetlenné vált Ukrajna – a korábban biztosított gyakorlatától eltérően – szűkítette az anyanyelven folyó tanulás lehetőségét, illetőleg az oktatási nyelv megválasztásának a jogát. A kárpátaljai magyarság érdekvédelmi szervezetei, oktatási és nyelvi jogi szakértői a jogszabály kapcsán kibontakozott vitában kezdettől fogva egyértelműen amellett foglaltak állást, hogy a törvény 7. cikke ellentétes Ukrajna Alkotmányának számos rendelkezésével, több ukrán törvénnyel, továbbá nem egyeztethető össze az ország nemzetközi kötelezettségvállalásaival (Csernicskó, 2018b).

Abstract. The article deals with the problematic issues of teaching the Ukrainian as the state language in general educational institutions with the Hungarian language of instruction in Transcarpathia from the point of view of the new Ukraine’s Law On Education and the Law On Supporting the Functioning of the Ukrainian Language as the State Language. These laws led to a rather intense political and legal discourse, in which Ukraine was criticized by both the representatives of national minorities, and the international institutions. The right to mother tongue medium education for national minorities (including Hungarians) the right to education in their mother tongue is ensured by the new laws only at the level of pre‐primary and elementary school. Minorities can study “one or more disciplines” in their mother tongue from the 5th grade only; other subjects are taught in the state language. Our article argue, that improvements in the study of the Ukrainian language in general education institutions with instruction in the languages of national minorities should be addressed in the system of language education, where the language of instruction is the mother tongue of students, and the state language is taught at a high level by specialists specially trained for such work.
Egy (nyelv)pedagógiai kérdés (nyelv)politikai vonatkozásai
Keywords: többnyelvűség; kisebbségek; Ukrajna